Biological ferroelectricity in human nail samples using Piezoresponse Force Microscopy. (1st November 2013) - Pal, M; Guo, R; Bhalla, A
<x xml:space="preserve">Abstract</x> Ferroelectric and piezoelectric-like behaviour has been detected in some biological samples in the past few years owing to the capability of the Piezoresponse force microscopy. This paper puts into perspective the electrical response of the human nail sample. The free end of the human nail plate has been studied and its lateral and vertical electrical response of the amplitude and phase has been shown. Reversal of the applied voltage has shown partial response on the phase reversal. Differences in dry and wet nail samples have been compared and their results discussed.